The role of institutional quality on fiscal consolidation in developing countries - Ng, Chee Hung; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This paper examines the effect of institutional quality on the effort of fiscal consolidation in developing countries during 1980-2008. The panel generalized method of moments (GMM) results indicate that better quality of institutions tend to reduce the deficit budget accounts and the debt-to-GDP ratios in developing countries. The stronger institutions allow these countries to involve in more fiscal expansionary programs as well as to achieve a higher sustainable level of debts.